2017
DOI: 10.1080/1028415x.2017.1348436
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced cognitive impairment in obesity can be reversed by vitamin D administration in rats

Abstract: Vitamin D improved hippocampus oxidative stress and inflammatory markers in HFD-induced obese rats and improved cognitive performance. Further studies are needed to better clarify the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 43 publications
2
34
1
Order By: Relevance
“…Indeed, it has been reported that obese rats treated with VD supplementation showed a reduced inflammatory biomarkers in the hippocampus. [ 11 ] Moreover, VD supplementation has also shown a significant improvement in the cognitive performance in elderly patients with senile dementia. [ 12 ] VD deficiency affects the endocrinal function as it leads to increasing insulin resistance and an alteration in pancreatic β-cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that obese rats treated with VD supplementation showed a reduced inflammatory biomarkers in the hippocampus. [ 11 ] Moreover, VD supplementation has also shown a significant improvement in the cognitive performance in elderly patients with senile dementia. [ 12 ] VD deficiency affects the endocrinal function as it leads to increasing insulin resistance and an alteration in pancreatic β-cell function.…”
Section: Introductionmentioning
confidence: 99%
“…; Hajiluian et al . ). Interestingly, previous data indicating that HFD‐induced behavioral changes and hippocampal dysfunction as a consequence of increased oxidative stress were obtained in the NNT‐deficient C57Bl/6J mice (Arnold et al .…”
Section: Discussionmentioning
confidence: 97%
“…HFDs are known to induce metabolic derangements that are accompanied by systemic inflammation, oxidative imbalance (Furukawa et al 2004;Studzinski et al 2009), cognitive decline, and behavioral alterations (Tucsek et al 2014;Cordner and Tamashiro 2015). Some of these alterations can be prevented by antioxidant administration (Alzoubi et al 2013(Alzoubi et al , 2018Chang et al 2014;Liu et al 2014;Hajiluian et al 2017). Interestingly, previous data indicating that HFD-induced behavioral changes and hippocampal dysfunction as a consequence of increased oxidative stress were obtained in the NNT-deficient C57Bl/6J mice (Arnold et al 2014;Krishna et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Vitamin D is thought to have antioxidant properties although involved mechanisms have not been fully described yet and further research is required [18,170]. Vitamin D, acting through its nuclear receptors, can stimulate the expression of genes coding for antioxidant enzymes such as SODs and GPxs [171]. It has also been confirmed that after exposure of the skin to UV radiation, calcitriol and its precursors increase p53 levels, which reduces intracellular ROS [172].…”
Section: Vitamin D-function and Antioxidant Effectmentioning
confidence: 99%